ІНФОРМАЦІЙНА КУЛЬТУРА ОСОБИСТОСТІ В УМОВАХ ІНФОРМАТИЗАЦІЇ СУСПІЛЬСТВА (Педагогіка вищої та середньої школи, 2022)
The article deals with the question offorming of information culture of a personality in the condition of swift informatization of society.